Legacy: untangling the lines of inheritance - Gunderson, Kirsten Rana, author; Lundberg, Thomas, advisor; Bates, Haley, committee member; Fahey, Patrick, committee member; Marvin, William, committee member (Colorado State University. Libraries, 2015)
My artwork aims to understand the nature of a legacy. From family history to material objects, to shared genes and shared obligations, I examine the intertwined threads linking people, events, and objects within my family. I seek answers to questions I have about myself and about those who have shaped me. I weave together the individual elements of my inquiry, assigning color and pattern to people, feelings, and memories. Imbued with qualities of family character and suffused with emotion, the robes are the final assembly of these components. These robes are an incarnation of my grandfather and of his complicated interactions with his family. He was a man who struggled with his own sense of identity. He had great hopes and aspirations, but anger, desire, and self-doubt often undermined his plans and relationships. By interpreting my grandfather's personal narrative into cloth, I hope to resolve his fractured legacy. These robes are not simply a tribute to my grandfather; they are my study of who he was and of what he has passed on to me. I, too, have the desire to live an extraordinary life, but there are restraints, and responsibilities to be met. The fibers and patterns in my weavings draw upon Viking textiles and the functional and spiritual needs they fulfilled. I seek to incorporate natural rhythms and forms, managing elements of chance as colors shift and watery patterns form. The robes are created to blend a sense of elements and the natural world, while creating parallels with human nature. I find inspiration in Norse cosmology and in the way humans try to answer questions about their lives, the world, and the universe. Like a weaving made of hundreds of fine yarns, a person is formed by what they inherit and learn from hundreds of people.
Thesis lacks images.